2000
DOI: 10.1364/josaa.17.000517
|View full text |Cite
|
Sign up to set email alerts
|

L/M cone ratios in human trichromats assessed by psychophysics, electroretinography, and retinal densitometry

Abstract: Estimates of the relative numbers of long-wavelength-sensitive (L) and middle-wavelength-sensitive (M) cones vary considerably among normal trichromats and depend significantly on the nature of the experimental method employed. Here we estimate L/M cone ratios in a population of normal observers, using three psychophysical tasks-detection thresholds for cone-isolating stimuli at different temporal frequencies, heterochromatic flicker photometry, and cone contrast ratios at minimal flicker perception--as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
101
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 40 publications
17
101
1
Order By: Relevance
“…From these data, L:M ratios can be calculated in trichromatic observers that are comparable with those obtained in psychophysical experiments (see Brainard et al, 2000;Kremers et al, 2000).…”
Section: Response Amplitude and Phase Versus Retinal Illuminancesupporting
confidence: 70%
See 1 more Smart Citation
“…From these data, L:M ratios can be calculated in trichromatic observers that are comparable with those obtained in psychophysical experiments (see Brainard et al, 2000;Kremers et al, 2000).…”
Section: Response Amplitude and Phase Versus Retinal Illuminancesupporting
confidence: 70%
“…For chromatic-mediated detection, the sensitivities for L-and M-cone isolating stimuli are generally equal (Krauskopf, 2000;Kremers et al, 2000). In line with this finding, most subjects reported greater discomfort when observing the flickering L-cone stimulus at higher luminances.…”
Section: Response Amplitude and Phase Versus Retinal Illuminancesupporting
confidence: 66%
“…The ratio between L-and M-cone driven responses at 30 Hz was found to be proportional to the ratio of L-to M-cone numbers in the retina (Brainard et al, 2000;Kremers et al, 2000). In four subjects (JK, BL, FH and RT) the measurements with 30 Hz modulation were performed (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the short-wavelength-sensitive-(S) cone submosaic has been relatively well characterized (Williams et al, 1981;de Monasterio et al, 1985;Ahnelt et al, 1987;Curcio et al, 1991), the organization of long-wavelength-sensitive (L) and middle-wavelength-sensitive (M) cones in the human retina has proven more elusive, because they exhibit no known morphological or histochemical differences and their pigments are 96% identical (Nathans et al, 1986). Several studies using indirect measurements have suggested that there are on average more L cones than M cones, with large intersubject variability (DeVries, 1946;Rushton and Baker, 1964;Cicerone and Nerger, 1989;Pokorny et al, 1991;Yamaguchi et al, 1997;Hagstrom et al, 1998;Brainard et al, 1999;Deeb et al, 2000;Kremers et al, 2000;Otake and Cicerone, 2000;Carroll et al, 2002). A limitation of these estimates is that they often involve the untested assumption that each M cone and each L cone contribute equally to the molecular, physiological, or psychophysical mechanisms being monitored to derive L:M ratio estimates.…”
Section: Introductionmentioning
confidence: 99%